The association of microbial activity with Fe, S and trace element distribution in sediment cores within a natural wetland polluted by acid mine drainage - Aguinaga O.E. (2019)
Natural recovery and remediation of acid mine drainage (AMD) reduces the generation of acidity and transport of trace elements in the runoff. A natural wetland that receives and remediates AMD from an abandoned copper mine at Parys Mountain (Anglesey, UK) was investigated for better understanding of the remediation mechanisms. Water column concentrations of dissolved Fe and S species, trace metal (loid)s and acidity decreased markedly as the mine drainage stream passed through the wetland. The metal (loid)s were removed from the water column by deposition into the sediment. Fe typically accumulated to higher concentrations in the surface layers of sediment while S and trace metal (loid)s were deposited at higher concentration within deeper (20–50 cm) sediments. High resolution X-ray fluorescence scans of sediment cores taken at three sites along the wetland indicates co–immobilization of Zn, Cu and S with sediment depth as each element showed a similar core profile. To examine the role of bacteria in sediment elemental deposition, marker genes for Fe and S metabolism were quantified. Increased expression of marker genes for S and Fe oxidation was detected at the same location within the middle of the wetland where significant decrease in SO42− and Fe2+ was observed and where generation of particulate Fe occurs. This suggests that the distribution and speciation of Fe and S that mediates the immobilization and deposition of trace elements within the natural wetland sediments is mediated in part by bacterial activity. © 2019 Elsevier Ltd